2018
DOI: 10.1002/jcp.27647
|View full text |Cite
|
Sign up to set email alerts
|

Growth arrest‐specific 5 attenuates cisplatin‐induced apoptosis in cervical cancer by regulating STAT3 signaling via miR‐21

Abstract: Cervical cancer is the most common cause of female cancer‐related mortality worldwide. Decreased expression of long noncoding RNA growth arrest‐specific 5 (GAS5) is found in human cervical cancer tissues and associated with poor prognosis. However, the studies on associations between GAS5 level and malignant phenotypes, as well as sensitivity to chemotherapeutic drug in cervical cancer cells are limited. In this study, overexpression of GAS5 in cervical cancer cells resulted in prohibited cell proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 53 publications
0
30
1
Order By: Relevance
“…GAS5 can act as the molecular spongy binding numerous microRNAs mutually but the observations in detail are still remained largely unclear. Negative regulation between GAS5 and microRNA-21 (miR-21) has been certificated in various tumors and other diseases for the GAS5 Exon 4 contains miR-21 binding sequence (Zhang et al, 2013;Song et al, 2014;Hu et al, 2016;Cao et al, 2017;Tao et al, 2017;Suo et al, 2018;Yao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…GAS5 can act as the molecular spongy binding numerous microRNAs mutually but the observations in detail are still remained largely unclear. Negative regulation between GAS5 and microRNA-21 (miR-21) has been certificated in various tumors and other diseases for the GAS5 Exon 4 contains miR-21 binding sequence (Zhang et al, 2013;Song et al, 2014;Hu et al, 2016;Cao et al, 2017;Tao et al, 2017;Suo et al, 2018;Yao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…82 GAS5 prohibited cell proliferation, colony formation, migration and invasion, and increased cell cycle arrest in Hela and Siha CC cells. 119 Overexpression of GAS5 inhibited cell proliferation, migration and invasion, induced cell apoptosis, and arrested cell cycle in A498 RCC cells as well. 35 Oral squamous cell carcinoma (OSCC) is the most common cancer of HNC.…”
Section: Biological Behaviorsmentioning
confidence: 93%
“…84 Moreover, GAS5 enhanced the activity of DPP-induced cell growth inhibition and apoptosis in DPP-resistance cell via GAS5/miR-21/E2F transcription factor 3 (E2F3)/STAT pathway in CC, suggesting that GAS5 could be a novel target for CC patients with DPP-resistance in clinical. 119 Overexpression of GAS5 enhanced radio-sensitivity in SiHa CC cells, while GAS5 knockdown decreased radiosensitivity in ME180 CC cells. 130 In-depth mechanism studies showed that GAS5 enhanced the radio-sensitivity of CC cells via inducing immediate early response 3 (IER3) through regulation of miR-106b expression.…”
Section: Molecular Mechanismsmentioning
confidence: 97%
“…Thus, cisplatin destroys the normal function of DNA in cancer cells and induces cells to enter the apoptotic process. 24,25 However, high-dose treatment of cisplatin causes severe side effects, including neurotoxicity, nephrotoxicity, gastrointestinal reactions and myelosuppression. 26,27 Therefore, reducing the dosage of cisplatin and increasing the sensitivity of CRC cells to cisplatin is important to improve the chemotherapy effect and patient compliance.…”
Section: Discussionmentioning
confidence: 99%